Faktor-Faktor yang Mempengaruhi Kinerja Dosen Pendidikan Biologi FKIP Universitas Ahmad Dahlan Yogyakarta - Nani Aprilia (Universitas Ahmad Dahlan, 2013)
This study aimed to reveal:(1) lecturers performance education biology in FKIP UAD and (2) the effects of working motivation, lecturers' main duties and working atmosphere on lecturers' performance educational biology FKIP UAD